Deliverables - Feinstein International Center (Tufts Archival Research Center, 2005)
In 2006 we focused primarily upon laying the groundwork and recruiting the faculty and staff to enable us to begin the intellectual and institutional change processes outlined above. We achieved most of our deliverables for 2006 and are extending several into 2007. However, the overall shape of our deliverables in the coming twelve months will differ substantially from those of the closing year. 2006 was about building the Center; 2007 is about putting it the change processes into action. The vast majority of our 2007 deliverables focus on research and education. Our change process is captured in seven key processes, as described in detail in our three year strategy. Under each of these processes we list here the milestones, outputs and impact we hope to realize in 2007.